Comparative Histopathological Effects of Intra-Articular Bevacizumab, Ranibizumab, and Aflibercept in Experimental Osteoarthritis - Raşit Emin Dalaslan; Mehmet Arıcan; Zekeriya Okan Karaduman; Mücahid Osman Yücel; Sönmez Sağlam; Fatih Demir; Mücahit Çelik (Journal of Clinical Medicine, 2026)
Background: Vascular endothelial growth factor (VEGF) has emerged as a potential therapeutic target in osteoarthritis (OA). Although several anti-VEGF agents are widely used in clinical practice, their comparative effects on osteoarthritic cartilage remain unclear. This study compared the histopathological effects of intra-articular bevacizumab, ranibizumab, and aflibercept in an experimental rat model of OA. Methods: Experimental OA was induced in 36 rats using anterior cruciate ligament transection. One month later, animals received two intra-articular injections of bevacizumab (2 mg/kg), ranibizumab (0.5 mg/kg), aflibercept (3.2 mg/kg), or saline at 3-week intervals. Histopathological evaluation was performed using the Osteoarthritis Research Society International (OARSI) grading and staging system by two blinded pathologists. The primary outcome was the total OARSI score. Group comparisons were performed using the Kruskal–Wallis test followed by Dunn–Holm post hoc analysis. Results: Three animals were lost during anesthesia and surgical induction of OA before treatment allocation, leaving 33 rats for analysis. Significant overall differences were observed among the groups for the primary outcome of total OARSI score (p = 0.026) and the secondary outcomes of OARSI grade (p = 0.042) and OARSI stage (p = 0.019). Ranibizumab demonstrated numerically lower OARSI grade and total scores than the control group, whereas both groups had the same median OARSI stage score. Bevacizumab showed numerically lower OARSI grade and total scores than the control group but a slightly higher median stage score. Pairwise analysis showed significantly lower OARSI stage and total OARSI scores in the ranibizumab group than in the aflibercept group, whereas no significant differences were observed between any treatment group and the control group after correction for multiple comparisons. Conclusions: Anti-VEGF agents demonstrated differential histopathological responses in experimental OA. Although no treatment significantly improved histopathological outcomes compared with the control group after adjustment for multiple comparisons, ranibizumab showed lower OARSI stage and total scores than aflibercept. These findings indicate that the evaluated anti-VEGF agents may not exert equivalent biological effects and warrant further investigation in adequately powered experimental studies.